DETERMINATION OF TENSILE MODULUS OF WOVEN-GLASS FIBRE REINFORCED POLYESTER COMPOSITES AND ITS DEGRADATION BY MEANS OF ULTRASONIC TESTING PULSE-ECHO METHODS - Alfian, Dedi
Woven fibre glass composites are widely used as structural components in civil infrastructure, automotive industry and ships. Composites can be degraded caused by interactions with the environment such as water vapor, temperature and uv light. Degradation can decrease modulus elasticity of the composite. Modulus elasticity is generally obtained from tensile test, but these test have limitation such as requiring specimen preparation and cannot be actually carried out in the field.. Theoretically, modulus elasticity can be obtained from ultrasonic testing utilizing the wave velocity. The purpose of this study is to determine the modulus of elasticity of woven fibre glass composites and its degradation through ultrasonic testing pulse-echo methods. Composite were made by hand-lay up method and compressed at room temperature to produce 38%, 41% and 46% fibre volume fraction. Composite degradation method was conducted by soaking the composites in boiling water until it reaches its saturation point. Ultrasonic testing was carried out using a straight and an angle probe along fiber direction and thickness direction of the composite. Determination of modulus elasticity utilizes the velocity of wave propation through twice the initial distance method. Modulus elasticity of ultrasonic testing was validated using the result of tensile test and composite micromechanics model. The results showed higher fiber volume fraction, resulted in higher velocity of the wave propagation of the composites. Modulus elasticity and its degradation in woven glass fibre composites can be obtained by means of ultrasonic testing pulse-echo method using both 0/straight and 90/angle probes. The use of straight probe resulted in error of the elastic modulus of 6 – 19%, while using the angle probe result error of the elastic modulus 2 – 9%. Determination of the elastic modulus reduction of the degraded composites showed a decrease of 9 – 11% using the straight probe and 5,2 – 7,5% using the angle probe.